Systematic Comparison of the Performances of De Novo Genome Assemblers for Oxford Nanopore Technology Reads From Piroplasm - Wang, Jinming; Chen, Kai; Ren, Qiaoyun; Zhang, Ying; Liu, Junlong; Wang, Guangying; Liu, Aihong; Li, Youquan; Liu, Guangyuan; Luo, Jianxun; Miao, Wei; Xiong, Jie; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Emerging long reads sequencing technology has greatly changed the landscape of whole-genome sequencing, enabling scientists to contribute to decoding the genetic information of non-model species. The sequences generated by PacBio or nanopore technologies must be assembled de novo before further analyses. Some new de novo assemblies have been developed to assemble long reads generated by nanopore sequencing technology. The performance of these assemblers has not been completely investigated. However, genome assembly is still a challenging task. We systematically evaluated the performance of nine de novo assemblers for nanopore sequencing data on different coverage depth datasets. Several metrics were measured to determine the performance of these tools, including N50 length, sequence coverage, runtime, easy operation, accuracy of genome and genomic completeness in varying depths of coverage. Based on the results of our assessments, the performances of these tools are summarized as follows: 1) Coverage depth has a significant effect on genome quality; 2) The level of contiguity of the assembled genome varies dramatically among different de novo tools; 3) The correctness of an assembled genome is closely related to the completeness of the genome. More than 30× nanopore data can be assembled into a relatively complete genome, the quality of which is highly dependent on the polishing using next generation data. Considering the results of our investigation, the advantage and disadvantage of each tool are summarized and guidelines of selecting assembly tools are provided under specific conditions.